Exploring the impact of window design and ventilation strategies on air quality and thermal comfort in arid educational buildings - Ayman Ragab; Mai Mostafa Hassieb; Abdelaziz Farouk Mohamed (Scientific Reports)
Abstract Natural ventilation plays a vital role in the design of educational buildings, as it directly influences thermal comfort and, consequently, student performance, achievement, and health. This study investigates the impact of window parameters and various ventilation scenarios on indoor natural ventilation, aiming to enhance indoor air quality and thermal comfort in educational facilities in Aswan, Egypt. An experimental case study was conducted using a HOBO MX CO2 data logger to measure air temperature, carbon dioxide (CO2) levels, and relative humidity. These parameters, along with the predicted mean vote (PMV), were analyzed through four distinct classroom scenarios simulated using the Design Builder software. The scenarios included: (1) single-side natural ventilation during air conditioning operation; (2) solely passive ventilation; (3) 20-minute cross-ventilation intervals between lectures; and (4) extended 60-minute cross-ventilation during lecture breaks to minimize disruptions. Results indicate that a window-to-wall ratio (WWR) of 20% with a window aspect ratio of 1:2 significantly improves air quality and thermal comfort. The findings suggest that windows should be opened for at least 60 min in summer and 20 min in winter, resulting in a temperature reduction of 1 to 2 °C and a 36% decrease in CO2 concentrations. Additionally, acceptable PMV values were maintained for 40% of the total classroom hours. This research offers practical recommendations to optimize air quality and thermal comfort in educational buildings, thereby supporting student health and academic success. The study introduces a novel approach by integrating window design and WWR to achieve the balance between improving thermal comfort and enhancing natural ventilation in hot, arid climates.